ECG abnormalities in chronic obstructive pulmonary disease exacerbation: can the ECG record still astound us? A prospective study - Lazovic Biljana; Zivotic Ivan; Dmitrovic Radmila; Jovičić Nevena; Simonovic Isidora; Milic Rade; Sarac Sanja (Egyptian Journal of Chest Disease and Tuberculosis)
Introduction/objective Chronic obstructive pulmonary disease (COPD) is a pulmonary disease characterized by persistent respiratory difficulties and impaired airflow. COPD patients have a higher risk for lung infections, like the flu or pneumonia, lung cancer, heart problems, weak muscles, brittle bones, depression, and anxiety.